Bancos comunitários de desenvolvimento: identificação de relações estratégicas de parceria - Frizon, Nayana (Universidade Federal de São Carlos, 2015)
This paper analysis the community development banks concept, understood as social technologies of solidarity finances, brought up to discussion under solidarity economy and Science, Technology and Society (STS) aspects. Whilst they involve intrinsic social benefits, community banks currently experience similar challenges. Within this context, the objective of this study is built upon the following research question: In what aspects do partnerships between the local community and supporting bodies contribute to strengthening activities of community banks for development, and, consequently, their sustainability? , it pursued identify the most meaningful partnerships for solving the experimented difficulties by the Banco Comunitário Nascente in São Carlos SP. To develop this paper, it had been made several workshops with the Banco Comunitário Nascente employees beyond a wide bibliographic revision and documentation analysis. Through the information achieved by the bibliographic research it was possible to comprehend the historic contest and identify events and actors (local and external) fundamental for solidarity economy existence and, there for, from the Banco Comunitário Nascente in the city. From the results obtained in the workshops it was possible to evince the principal problems to be faced, such as analyse the impacts of the local and external actors in front of these problems. These informations sum made possible a appropriate methodology construction to identify the strategical partnerships to be fomented/developed by the workers, to grant the resolution of the problems experienced during their activities at the community bank. From this analysis logic, the following master's dissertation provides aids (methodological and technical) to solve the difficulties experimented by the Community Development Banks under the potentialities of the partnerships relationships bias.
Keywords: Economia solidária; Finanças; Parceria; Subsídios metodológicos; Bancos comunitários; Community development banks; Solidarity economy; Solidarity finance; Partnerships; Methodological allowance; OUTROS